Multiple Cemento-Ossifying Fibroma: A Sign of Hyperparathyroidism-Jaw Tumour Syndrome - Nurul Inaas Mahamad Apandi; Nor Nazaliza Basri; Ajura Abdul Jalil; Md Arad Jelon (Hindawi Limited, 2023)
Hyperparathyroidism-jaw tumour (HPT-JT) syndrome is a rare autosomal dominant disease. It is caused by a gene mutation of the tumour suppressor gene CDC73 that encodes for parafibromin. This syndrome predisposes to a triad occurrence of multiple maxillary or mandibular cemento-ossifying fibroma, parathyroid adenoma or carcinoma, and renal and uterine tumours. In this study, we report a case of HPT-JT occurring in a 30-year-old male patient.